TINGKAT OKUPASI DAN PERUBAHAN TEKNOLOGI ARTEFAKTUAL DI KOMPLEKS GUA PRASEJARAH BELLAE, KAB. PANGKEP, SULAWESI SELATAN - nfn Supriadi (Balai Arkeologi Provinsi Sulawesi Utara, 2018)
Once period residential caves in South Sulawesi is a period play of important role in the framing national history. The study has been done indicating that it’s period has a long time range between 30,000 BP - 1500 BP. The time range allows residential and occupational repetition in one place , either by the same kind of man as well as by different kinds of people. Prehistoric cave complex Bellae is an area that has been inhabited or occupational evidence ever undertaken by humans .The purpose of this study is to observe at the occupational level of each layer of culture that has ever happened in the Prehistoric Caves Complex Bellae. Three caves were used as samples to do the excavation which represents the amount of 22 caves. The selection was made based on the consideration of the location of the cave , the cave shape, and surface findings . Excavations carried out by using a box model with a deepening technique using spit .The results of research showed that human occupation in Prehistoric Caves Complex Bellae the most intense occurred in the middle layer of culture. Displacement of each layer of culture , based on the findings of kitchen waste is always decreasing occupation . Food gathering system utilizing the surrounding environment of the marine environment, both freshwater and salty. The food gathering was influenced by season. From the results of the excavation is also seen that prior to human consumption of shellfish , the protein source is derived from small animals . Changes in the cultural layer then accompanied by artefaktual changes. The most obvious artifacts are finding pottery the younger cultural layers.